High-power narrow-linewidth diode laser based on external cavity feedback technology for Yb: YAG pumping. (1st December 2022) - Han, Jinliang; Zhang, Jun; Shan, Xiaonan; Zhang, Yawei; Peng, Hangyu; Qin, Li; Wang, Lijun
Abstract: An external cavity feedback structure based on volume Bragg grating is introduced to realize the spectral stabilization and linewidth narrowing of a diode laser with a central wavelength of 968.668 nm and a spectral linewidth of 0.405 nm. A diode laser source producing 1.443 kW power from an output fiber with a core diameter of 1000 μ m is achieved by using a spatial beam, combining, and polarization multiplexing technologies. The external cavity feedback and fiber coupling efficiencies exceed 93% and 90%, respectively. Such a high-power narrow-linewidth diode laser can be applied in Yb: YAG pumping efficiently and stably.